2018
DOI: 10.1038/s41598-018-36156-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeted expression of Vitreoscilla hemoglobin improves the production of tropane alkaloids in Hyoscyamus niger hairy roots

Abstract: Under hypoxic conditions, the expression of Vitreoscilla hemoglobin (VHb) in plants is proposed to increase the productivity of certain oxygen-requiring metabolic pathways by promoting the delivery of oxygen. Tropane alkaloids (TAs) are a class of important plant secondary metabolites with significant medicinal value; the final step in their biosynthesis requires oxygen. Whether heterologous expression of VHb, especially in different subcellular compartments, can accelerate the accumulation of TAs is not known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 52 publications
1
10
0
Order By: Relevance
“…It was strongly demonstrated that the concentration sugar was greatly enhanced by over expression of the VHb and on the other hand, the cell growth was almost the similar [47]. Some studies showed that expression of vgb gene was effective on the production several metabolites [10,38,[48][49][50]. In addition, vgbstrain showed more or less similar results with vgb + in both intra-and extracellular vitamin production.…”
Section: Resultsmentioning
confidence: 99%
“…It was strongly demonstrated that the concentration sugar was greatly enhanced by over expression of the VHb and on the other hand, the cell growth was almost the similar [47]. Some studies showed that expression of vgb gene was effective on the production several metabolites [10,38,[48][49][50]. In addition, vgbstrain showed more or less similar results with vgb + in both intra-and extracellular vitamin production.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical transformation is conceptualized as two concerted reactions: (i) the hydroxylation of atropine followed by (ii) the cyclization of anisodamine to form an epoxide between the carbon atoms C6 and C7. The two reactions are assumed to be catalyzed in vivo by a single enzyme: hyoscyamine-6β-hydroxylase (H6H, EC 1.14.11.11) [28]. H6H has been cloned from different Solanaceae [29].…”
Section: Discussionmentioning
confidence: 99%
“…So far, many attempts have been made to induce hairy roots with specific traits, most of which are based on genetic engineering techniques that allow plant material with increased utility values to be obtained. A good example of this approach is the heterologous expression of Vitreoscilla hemoglobin in plastids using the pVHb-RecA construct, leading to increased production of hyoscyamine and scopolamine in Hyoscyamus niger L. in vitro transgenic plant cultures [62]. Another is the possibility of affecting the increase in the content of glycyrrhizic acid by overexpression of the β-amyrin synthase gene in hairy roots of Glycyrrhiza uralensis Fisch.…”
Section: Hairy Rootsmentioning
confidence: 99%